Improvement of Doxorubicin Efficacy by Conjugating to pH‐Sensitive Copolymer‐Coated Magnetic Nanoparticles. Issue 1 (10th February 2016) - Siami, Fatemeh; Ahmadpanahi, Homayon; Heidarinasab, Amir; Moniri, Elham; Akbarzadeh, Azim
ABSTRACT: Chemotherapy is one of the main treatment regimens for cancer therapy. Efficacy of chemotherapy is limited issues such as nonspecific cytotoxicity, poor aqueous solubility, and bioavailability. Targeted drug delivery is an ideal strategy to overcome these barriers. Fe3 O4 magnetic nanoparticles (MNPs) as a great drug delivery system have drawn considerable attention. Functionalized nanoparticles (NPs) here were synthesized by the coprecipitation method and characterized by thermogravimetric analysis and transmission electron microscopy techniques. An anticancer agent, doxorubicin (DOX), was loaded onto the NPs and then the release behavior and cytotoxicity effects of nanodrug were determined. The pH‐sensitive behavior of drug release was observed. While the total loaded drug was released at pH 1.2 in 30 min, the amount of drug release was equal to 8% in pH 7 after 8 h. The drug‐loading efficiency was found to be 88%. Also, NPs potentiate the efficacy of the drug by increasing its cytotoxicity, in which IC50 of 57 and 39 μM for the nanodrug and drug was estimated, respectively. In conclusion, the results of the study showed that MNPs are promising vehicle for DOX delivery.